Assessing temporal variability in durum wheat performance and stability through multi-trait mean performance selection in Mediterranean climate - Sellami, Mohamed Houssemeddine; Di Mola, Ida; Ottaiano, Lucia; Cozzolino, Eugenio; De Vita, Pasquale; Mori, Mauro (Frontiers in Agronomy, 2024)
Durum wheat, a staple crop in Italy, faces substantial challenges due to increasing droughts and rising temperatures. This study examines the grain yield, agronomic traits, and quality of 41 durum wheat varieties over ten growing seasons in Southern Italy, utilizing a randomized complete block design. Notably, most varieties were not repeated between trials and 45% of the data was missing. The results indicate that the interaction between genotype and environment (GEI) significantly impacted all traits. High temperatures, elevated vapor pressure deficit (VPD), and water deficits severely affected yield and quality during warm years, while cooler years with favorable water availability promoted better growth and higher yields. Broad-sense heritability (H²) was generally low, suggesting that environmental factors played a major role in the observed traits. However, some traits, such as grain yield, ears per square meter, plant height, bleached wheat, thousand-grain weight, and hectoliter weight exhibited moderate to high heritability of the mean genotype (h²mg), indicating their potential for effective selection in breeding programs. Correlation analyses revealed strong connections between certain traits, such as protein content, and gluten index as well as between grain yield, and spike per square meter. Using the Multi-Trait Mean Performance Selection (MTMPS) index, the study identified six top-performing varieties. Among these, Antalis (G4) and Core (G18) consistently demonstrated strong adaptability and stability across different environments, particularly in hotter, drier conditions. Furio Camillo (G31) also exhibited valuable traits. This study highlights the challenges and complexities of breeding durum wheat for improved yield and quality in the face of climate change.